On the relationship between preferential and multilateral trade liberalization : the case of customs unions - Saggi, Kamal (2013)
Compares equilibrium outcomes of two types of trade liberalization. Looks at bilateralism where countries choose whether to liberalise trade preferentially via a customs union (CU) multilaterally, or not at all; multilateralism in which countries cann form CUs and can only undertake non-discriminatory trade liberalisation. Isolates circumstances where the option to form CUs helps further the cause of multilateral liberalisation as well as where it does not.